3D printable composite dough for stretchable, ultrasensitive and body-patchable strain sensors. Issue 31 (5th June 2017) - Kim, Ju Young; Ji, Seulgi; Jung, Sungmook; Ryu, Beyong-Hwan; Kim, Hyun-Suk; Lee, Sun Sook; Choi, Youngmin; Jeong, Sunho
Abstract : We demonstrate 3D-printed, highly-sensitive strain sensor devices by formulating the 3D-printable dough including hybrid carbon composites. Abstract : The recent development of strain sensor devices which can actively monitor human body motion has attracted tremendous attention, for application in various wearable electronics and human–machine interfaces. In this study, as materials for strain sensor devices, we exploit the low-cost, carbon-based, 3-dimensional (3D) printable composite dough. The dough is prepared via a chemical method based on the formation of electrostatic assemblies between 1-dimensional, amine-functionalized, multi-walled carbon nanotubes and 2-dimensional graphene oxides. The resulting composite dough has an extremely high storage modulus, which allows a vertically-stackable, 3D printing process for fabricating strain sensor devices on various dense, porous and structured substrates. The device performance parameters, including gauge factor, hysteresis, linearity, and overshooting behavior are found to be adjustable by controlling the printing process parameters. The fabricated strain sensor devices demonstrate the ability to distinguish actual human body motions. A high gauge factor of over 70 as well as other excellent device performance parameters are achievable for the printed sensor devices, and even small strains, below 1%, are also detectable by the fabricated sensor devices.